THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND COMPENSATION TOWARDS MOTIVATION AND ITS IMPLICATIONS ON ORGANIZATIONAL PERFORMANCE AT THE EDUCATION AND TRAINING CENTER OF THE MINISTRY OF COMMUNICATION AND INFORMATION - Adhi, Beny; Aima, M. Havidz (Dinasti Publisher, 2021)
This research has purposes to discover and analyze further relates to the impact which is caused by transformational leadership and compensation towards motivation and its implications for organizational performance at the Education and Training Center of the Ministry of Communication and Information Technology. The current research method used was quantitative research with a causal method. The population and sample in this research amounted to 42 respondents who are civil servants and PPNPN employees at the Education and Training Center of Ministry of Communication and Information. The data analysis method used SEM-PLS. And the results showed that transformational leadership and compensation had a positive and significant impact both simultaneously and partially in order to increase the motivation. Transformational leadership, compensation and motivation had a positive and significant impact either simultaneously or partially in enhancing organizational performance. Motivation could play as a mediator in influencing the relations of transformational leadership and compensation to organizational performance.